On the hysteresis of argon adsorption in a uniform closed end slit pore - Fan, Chunyan; Do, D.; Nicholson, D. (Academic Press, 2013)
We present a molecular simulation study of adsorption and desorption in slit mesopores of uniform width with one end closed and explore the effects of pore dimensions (width and length), temperature and surface affinity on the hysteresis loop: its position, lower and upper closure points, area and shape. Our results show that the metastability, brought about by structural change in the adsorbate, is the reason for the existence of hysteresis, and contrast with reports suggesting that reversibility invariably prevails for adsorption in closed end pores. The shape, area and position of the hysteresis loop are complex functions of pore width, length and temperature. We establish a parametric map of the boundary separating reversible and hysteretic regions. Our simulation results also show a number of interesting observations that have not been previously reported or generally recognised: (1) the fluid within the core of the pore behaves like a bulk liquid as the pore is progressively filled, via the movement of the meniscus from the closed end to the pore mouth, but as the pore fills, the fluid in the core becomes structured, (2) the shape of the meniscus changes as adsorption progresses but is constant during desorption because of the constant thickness of the adsorbed layer in the two-phase region, (3) the hysteresis loop is larger for a longer pore, (4) the area of the hysteresis loop increases with pore width up to a certain width, beyond which it decreases and finally disappears, (5) as temperature approaches the critical hysteresis temperature, the hysteresis loop area decreases, but it retains its Type H1 character. © 2013 Elsevier Inc.